Trabalho docente e sofrimento mental: um estudo em uma escola pública do Estado de São Paulo - Pereira, José Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to analyze the occurrence of mental suffering (MS) related to work in teachers of a public school in the State of São Paulo, in the city of Franca, Brazil. Mental suffering is constituted by a variety of symptoms that result from the gradual sickening. In spite of not yet having become a mental illness, MS symptoms are often seen as unbearable, having physical and psychic effects that can lead professionals to work absence. Since it is of difficult detection due to having diffuse and varied symptoms and, mainly, for not being adequately recognized by its subjects and, not rarely, by health professionals, MS has taken teachers to the adoption of individual and palliative measures in its management, which results in work leaves, abandonment and voluntary dismissals. Precarious work in teaching, inspires an investigation that reveals the underlying ideologies of the capitalist system and offers elements for the understanding of the sickening due to work. The deliberate confusion that is established in the search for the real causes of MS, lead teachers and other education professionals to self-blaming, assuming as natural the characteristics of a sickening profession that affects subjectivity, changes the ontological meaning of work and education and inserts students and teachers in a system that turns education into one more object to be consumed. MS is in this research approached from Occupational Health field. Bibliographic studies about Education in the capitalist system were carried out as well as on the sickening processes related to work, having as interlocutors, mainly, Christophe Dejours, Louis Le Guillant and Seligmann-Silva. Semi-structured interviews were also carried out with teachers selected from their functional situations in public work, having as a goal to identify MS, approach its causes and verify how teachers face and express this circumstance. The content analysis...

Esta pesquisa objetiva analisar a ocorrência do sofrimento mental (SM) decorrente do trabalho de professores em uma escola pública estadual paulista no município de Franca, SP. O SM é composto por uma ampla gama de sintomas decorrentes do processo de adoecimento gradativo. Apesar de ainda não ter atingido o status de doença, o SM inflige um quadro tido, muitas vezes, como insuportável, com reflexos físicos e psíquicos que geralmente levam os profissionais ao afastamento do trabalho. Por ser de difícil detecção em função da sintomatologia difusa e variada e, principalmente, por não ser devidamente reconhecido pelos próprios sujeitos e, não amiúde, pelos profissionais da saúde, o SM tem levado os professores à adoção de medidas individuais e paliativas em seu gerenciamento e que, não raro, descambam em licenças, abandono e exoneração de cargos. A precarização do trabalho docente inspira uma investigação que desvele as ideologias subjacentes ao sistema capitalista e forneça elementos para a compreensão do fenômeno do adoecimento no magistério. A proposital confusão que se estabelece na busca das causas reais do SM leva professores e outros profissionais da educação a processos de autoculpabilização e a assumirem como naturais, as características de uma profissão que adoece, atinge negativamente a subjetividade do trabalhador e deturpa o sentido ontológico do trabalho e da educação, inserindo alunos e professores em um sistema que transforma a educação em mais uma mercadoria a ser consumida via mercado. O SM é, nesta pesquisa, abordado a partir do campo da Saúde do Trabalhador. Foram feitos estudos bibliográficos acerca da Educação no sistema capitalista e dos processos de adoecimento decorrentes do trabalho, tendo como interlocutores, principalmente, Christophe Dejours, Louis Le Guillant e Seligmann-Silva. Foram realizadas entrevistas semiestruturadas com...
Keywords: Serviço social; Professores - Brasil; Escolas públicas - São Paulos (Estado); Ambiente de sala de aula - Aspectos psicológicos; Doenças profissionais - Educação; Franca (SP) - Educação; Saúde do trabalhador; Social service